Determination of shelf-life of vacuum-packed sea bream (Sparus aurata) fillets using chitosan-microparticles-coating. Issue 1 (1st January 2020) - Khemir, Meriam; Besbes, Nadia; Khemis, Ines Ben; Di Bella, Calogero; Lo Monaco, Daniela; Sadok, Saloua
ABSTRACT: Chitosan-microparticles (CM)-coating (CMC) effect on quality and shelf-life of vacuum-packed sea bream ( Sparus aurata ) fillets was investigated at 0.2% and0.5% (w/w) doses comparatively to untreated control, during refrigerated storage (24 days). Analysis concerned total mesophilic bacteria counts (TMC), total psychrophilic bacteria counts (TPC), proximate composition, pH, total volatile basic nitrogen (TVB-N), trimethylamine (TMA), thiobarbyturic acid (TBA), and fatty acids (FA). Two-way ANOVA and multiple comparison were applied, factors being storage time and treatment. Bacterial counts exceeded the limit in control but remained below in CMC lots. All of TVB-N, TMA and TBA increased faster and reached higher values in control compared to CMC lots, with dose-dependent effect. CMC preserved quality in terms of proximate composition and FA. The 0.5%-CM dose prolonged the shelf-life up to 12 days, corresponding to a two folds extension. CMC showed antimicrobial and antioxidant properties and should be recommended for preserving the quality of fish fillets. Graphical abstract: uf0001